Factors Affecting The Success of Exclusive Breastfeeding Among Mothers Recovered From Covid-19 - Ulfatul Latifah; Nora Rahmanindar; Ardhi Henda Karmandika (Media Kesehatan Masyarakat Indonesia, 2024)
Exclusive breastfeeding for the first 6 months and continued breastfeeding with complementary foods up to 2 years are emphasized by the World Health Organization. Amid the COVID-19 pandemic, maternal concerns about virus transmission through breastfeeding have surfaced. Despite these concerns, breastfeeding remains the primary recommendation due to its manifold health benefits. This research, conducted in Tegal City's Margadana sub-district, investigates factors influencing exclusive breastfeeding success among mothers recovered from COVID-19. Using an analytical observational design with a cross-sectional approach, the study explores the link between COVID-19 symptoms in infants and exclusive breastfeeding success, revealing a significant correlation (p-value=0.042). Conversely, breast milk production shows no significant association with exclusive breastfeeding success (p-value=0.144). Notably, spousal and family support emerges as pivotal, exhibiting a significant association with exclusive breastfeeding success (p-value=0.003). However, there is no significant relationship between healthcare provider support during breastfeeding and adherence to 6-month exclusive breastfeeding (p-value=0.456). The findings underscore the importance of breastfeeding during post-COVID-19, balancing potential virus transmission risks against the established breastfeeding health benefits. The study concludes by advocating for further research to comprehensively understand and address complexities of exclusive breastfeeding in the post-COVID-19 context, offering insights for healthcare practitioners and policymakers.